British values and identity among young British Muslims in Tower Hamlets: understandings and connections. Issue 4 (18th December 2017) - Green, Finlay
Abstract : Purpose: The purpose of this paper is to provide a platform for young British Muslims in Tower Hamlets to share their perspectives on British values and identity, in light of the increased pressure schools are facing to actively promote "British values". Design/methodology/approach: Three focus groups were convened of 16-18 year olds, two all-male (one with five and one with six participants) and one all-female (five participants). Discussions were audio recorded with the data subjected to a form of thematic analysis that divided the raw data into three different categories: individual, group and group interaction data. Findings: All but one of the participants defined themselves as British, largely due to a strong connection with British values. A minority felt this understanding was reflected back to them by society. However, the majority felt that, as ethnically Bengali and as Muslims, the opposite was the case. By judging the strength of an individual's Britishness against the strength of their adherence to British values the government's British values agenda is only serving to reinforce the isolation of those that feel excluded. Originality/value: While the identities of young people, British people, and Muslims have been widely explored, there is little research that looks at the intersection of all three.